Diagnostic efficacy of myeloperoxidase to identify acute coronary syndrome in subjects with chest pain. (June 2013) - Granér, Marit; Tikkanen, Emmi; Rimpilä, Olga; Tikkanen, Helena; Ripatti, Samuli; Lokki, Marja-Liisa; Nieminen, Markku S.; Taskinen, Marja-Riitta; Sinisalo, Juha
Abstract Background. Early diagnosis of acute coronary syndrome (ACS) is frequently a challenging task. Aims. To assess the role of novel biomarkers to identify ACS. Methods. Concentrations of lipids, lipoproteins, oxidized LDL (oxLDL), high-sensitivity C-reactive protein (hsCRP), paraoxonase-1 (PON1), secretory phospholipase A2 (sPLA2), and myeloperoxidase (MPO) were measured in 703 patients (mean age 65.5 ± 11.2 years; 422 men, 281 women) without diabetes mellitus assigned to coronary angiogram. The subjects were divided into three groups: ACS (n = 242), stable angina pectoris (SAP) (n = 242), and normal coronary artery (NCA) (n = 219). Results. HDL-cholesterol (HDL-C) (P < 0.001) and apolipoproteinA-I concentrations (P < 0.0001) were lowest in subjects with ACS. LDL-C (P = 0.008) and non-HDL (P < 0.0001) were higher in the ACS group than in the SAP group. Leukocyte count (P < 0.0001), oxLDL (P < 0.05), hsCRP (P < 0.001), sPLA2 (P < 0.05), and MPO (P < 0.0001) were highest in the ACS group. In multivariate models, comprising all biomarkers, elevated level of MPO had the best discriminatory power to identify patients with ACS. Receiver-operating characteristic curve with and without MPO comparison differed significantly (P = 0.03 for both ACS versus NCA and ACS versus SAP). Conclusion. Our study shows that ACS associates with low HDL-C and biomarkers of oxidative stress and inflammation. The addition of MPO in biomarker panels might improve diagnostic accuracy for ACS.